CAU-17 / BiOBr composite photocatalyst as well as preparation method and application thereof

By growing BiOBr in situ on the CAU-17 matrix, forming the CAU-17/BiOBr composite photocatalyst, the problem of insufficient interfacial interaction between BiOBr/MOF composite materials is solved, and its photocatalytic activity and adsorption ability are significantly improved, thus achieving the Efficient degradation of organic dyes.

CN119425805APending Publication Date: 2025-02-14GUANGXI UNIV FOR NATITIES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411697895.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing BiOBr/MOF composite materials have low interfacial interactions during photocatalysis, resulting in low recombination and charge transfer efficiency of carriers, limiting their photocatalytic activity and adsorption ability.

Method used

By using CAU-17 as the matrix, Bi3+ is uniformly adsorbed on the surface of CAU-17, and then adding a Br source, BiOBr grows in situ on CAU-17 through solvothermal reaction, forming a CAU-17/BiOBr composite photocatalyst, realizing BiOBr and CAU-17's close interface contact.

Benefits of technology

The separation efficiency and specific surface area of ​​the interfacial photogenerated electron-hole pair are significantly improved, the recombination of carriers is reduced, the photocatalytic degradation performance and adsorption capacity are enhanced, and the rhodamine B of 99.0%-99.8% and 97.0%-97.8 are achieved. % degradation rate of ciprofloxacin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425805A_ABST
    Figure CN119425805A_ABST
Patent Text Reader

Abstract

The invention discloses a CAU-17 / BiOBr composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The preparation method comprises the following steps: by taking CAU-17 as a matrix, adding a Bi < 3 + > source, enabling Bi < 3 + > to be uniformly adsorbed on the surface of the CAU-17, then adding a Br source, enabling generated BiOBr to grow on the CAU-17 in situ through solvothermal reaction, and fixing the BiOBr on a framework of the CAU-17, so as to obtain the CAU-17 / BiOBr composite photocatalyst. The structure of the catalyst is a nanorod-shaped structure, and a CAU-17 nanorod is uniformly coated with a BiOBr nanosheet. The preparation method of the catalyst comprises the following steps: (1) preparing CAU-17; and (2) preparation of the CAU-17 / BiOBr. In the prepared catalyst, CAU-17 is in close contact with a BiOBr interface, separation of photo-induced electron-hole pairs on the interface is accelerated, and the specific surface area is increased, so that recombination of carriers at the interface due to non-close contact of a heterogeneous interface is overcome, and the photocatalytic activity of degrading organic dye is remarkably enhanced; the photocatalyst has good photocatalytic degradation capability on RhB and CIP, and the removal rates of the RhB and the CIP are 99.44% and 97.46% respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and specifically relates to a CAU-17 / BiOBr composite photocatalyst and a preparation method and application thereof. Background Art

[0002] With the development of industry, water pollution affects all aspects of people's lives. Photocatalysis is an effective and promising method to remove toxic and difficult-to-degrade organic dyes from industrial wastewater, in which the separation of photogenerated carriers and the effective absorption of dye molecules are crucial in the degradation process. Porous crystalline metal-organic frameworks (MOFs) have attracted widespread attention in the field of energy and environment due to their flexible coordination environment, adjustable electronic structure and strong adsorption capacity for small molecules. However, the direct use of MOFs has great limitations. Their charge separation efficiency is much lower than that of traditional photocatalysts, and some intrinsic functions are masked or not fully integrated. The development of some efficient inorganic semiconductor / MOF-based heterojunctions such as TiO2@MOF, CdS-NRs / MOF, g-C3N4 / MOF and BiOBr / MIL-53(Fe) can significantly improve their photocatalytic performance. CAU-17 is a kind of porous Bi-based MOF. Its microstructure is hexagonal prisms with 5 kinds of microporous one-dimensional channels. However, the light absorption range is limited. The problem of light absorption range can be improved by forming a heterojunction with other materials or using it as a carrier to form a Bi-based semiconductor heterojunction.

[0003] Bismuth oxybromide (BiOBr) not only has a unique hierarchical structure, namely [Bi2O2] 2+The bibromine layer is staggered and distributed, and exhibits excellent optical and catalytic properties in photocatalytic energy conversion and environmental remediation. The special layered structure can generate an internal electric field, which is beneficial to the separation and migration of photogenerated charge pairs to a certain extent. At the same time, BiOBr can effectively absorb visible light due to its suitable band gap (2.4-2.9eV). Patent Publication No. CN 118807847 A discloses a method for radiative synthesis of Bi0Br / MOF composite materials and its application. The method uses ionizing radiation to grow MOF on the surface of BiOBr. The heterojunction structure formed by BiOBr and MOF can inhibit the recombination of carriers, improve the efficiency of charge separation and transfer, and effectively enhance the photocatalytic CO2 reduction ability. And the document "Bi-MOF-derived hollow BiOBr nanorods for efficient photocatalytic degradation of ciprofloxacin" discloses a method for designing and preparing hierarchical hollow BiOBr nanorods composed of multiple layers of ultra-thin nanosheets using MOF (CAU-17) as a template. However, the method uses MOF material as a sacrificial template to provide a structural framework for the growth of BiOBr material. Although a catalyst with structural performance superior to that of ordinary BiOBr was prepared, the MOF material was consumed during the reaction and the BiOBr / MOF heterojunction was not successfully constructed. At the same time, the adsorption performance was not significantly improved.

[0004] Due to the adjustable pores and structural flexibility of MOFs, as well as the ability to increase their specific surface area, BiOBr / MOF composites exhibit excellent chemical stability and outstanding ability to degrade organic pollutants in water under visible light irradiation. However, most of the existing BiOBr / MOF composites are synthesized by physical mixing or co-precipitation of BiOBr and MOF precursors. These processes usually produce insufficient chemical interactions between BiOBr and MOF, and the loose contact at the heterointerface of the two materials limits the transfer of photogenerated electron-hole pairs and increases the recombination of carriers at the interface. The optimized hierarchical structure is expected to improve the interfacial interaction between BiOBr and MOF through in situ growth, giving BiOBr / MOF composites great potential for photocatalytic activity. Therefore, precisely controlling the kinetics by designing BiOBr / MOF heterostructures to hinder the reconnection of photogenerated charges and increase the number of reaction sites is crucial to improving the adsorption capacity and rapid degradation rate of the catalyst. Summary of the invention

[0005] In view of the above problems, the present invention provides a CAU-17 / BiOBr composite photocatalyst and a preparation method and application thereof. CAU-17 is used as a matrix to support the growth of BiOBr. CAU-17 is in close contact with the BiOBr interface. The obtained CAU-17 / BiOBr composite photocatalyst has a large number of active species, a fast interface charge transfer rate, and good photocatalytic degradation performance.

[0006] The present invention is achieved through the following technical solutions:

[0007] A CAU-17 / BiOBr composite photocatalyst, with CAU-17 as the matrix and Bi 3+ After the source, make Bi 3+ It is uniformly adsorbed on the surface of CAU-17, and then a Br source is added to make the generated BiOBr grow in situ on CAU-17 through a solvothermal reaction, and BiOBr is fixed on the framework of CAU-17 to obtain a CAU-17 / BiOBr composite photocatalyst.

[0008] Furthermore, the structure of the CAU-17 / BiOBr composite photocatalyst is a nanorod structure, and the BiOBr nanosheets are uniformly coated on the CAU-17 nanorods; the current density of the transient photocurrent response of the CAU-17 / BiOBr composite photocatalyst is 11.2-11.3 μA / cm 2 .

[0009] A method for preparing the CAU-17 / BiOBr composite photocatalyst as described above comprises the following steps:

[0010] (1) Preparation of CAU-17: Bi(NO3)3·5H2O and trimesic acid were added to anhydrous methanol and stirred to dissolve at room temperature. The resulting mixed solution was transferred to a reactor for solvothermal reaction. After the reaction was completed, the product was collected by filtration and washed to obtain CAU-17.

[0011] (2) Preparation of CAU-17 / BiOBr: CAU-17 was added to ethanol and dispersed completely by ultrasound to obtain suspension A. Bi(NO3)3·5H2O was dissolved in ethylene glycol and subjected to ultrasound to obtain solution B. Solution B was slowly dripped into suspension A and stirred to obtain suspension C. NaBr was dissolved in water and then dripped into suspension C. Stirring was continued and the obtained suspension D was transferred to a reactor for solvothermal reaction. After the reaction was completed, the suspension was cooled to room temperature and centrifuged and washed to obtain a CAU-17 / BiOBr composite photocatalyst.

[0012] Furthermore, in step (1), the mass ratio of Bi(NO3)3·5H2O to trimesic acid is 1:4-6; the mass ratio of Bi(NO3)3·5H2O to anhydrous methanol is 5 mg:1.5-3 mL.

[0013] Furthermore, in step (1), the temperature of the solvent thermal reaction is 110 to 130° C., and the time is 22 to 24 hours.

[0014] Furthermore, in step (2), the mass ratio of CAU-17 to ethanol is 5 mg:1-2 mL; the mass ratio of Bi(NO3)3·5H2O to ethylene glycol is 48.5 mg:1-2 mL; and the mass ratio of CAU-17 to Bi(NO3)3·5H2O is 5:48-50.

[0015] Furthermore, in step (2), the mass ratio of NaBr to CAU-17 is 8 to 9:5.

[0016] Furthermore, in step (2), the temperature of the solvent thermal reaction is 150-170° C., and the time is 10-12 hours.

[0017] An application of the CAU-17 / BiOBr composite photocatalyst as described above is to apply the CAU-17 / BiOBr composite photocatalyst to photocatalytic degradation of rhodamine B and ciprofloxacin.

[0018] Furthermore, the degradation rate of the CAU-17 / BiOBr composite photocatalyst for rhodamine B is 99.0-99.8%, and the degradation rate for ciprofloxacin is 97.0-97.8%.

[0019] Preparation principle of the CAU-17 / BiOBr composite photocatalyst of the present invention:

[0020] (1) Preparation of CAU-17: Bi(NO3)3·5H2O and trimesic acid (H3BTC) were added to anhydrous methanol for a hydrothermal reaction. During this process, the MOF structural skeleton was formed by Bi ions and bridged by the organic ligand H3BTC to obtain a Bi-based MOF with a specific topological structure, namely CAU-17.

[0021] (2) Preparation of CAU-17 / BiOBr: CAU-17 was used as the matrix. The large pores and good adsorption capacity of CAU-17 were utilized to adsorb Bi ions in the Bi(NO3)3·5H2O solution into the pores and surface of CAU-17. Then NaBr was added to generate BiOBr that grew in situ on CAU-17 through a solvothermal reaction. The BiOBr was fixed on the framework of CAU-17, thus constructing a CAU-17 / BiOBr heterostructure with a large specific surface area. CAU-17 / BiOBr exhibited effective charge separation and increased adsorption capacity.

[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0023] 1. The present invention uses CAU-17 as the matrix and adds Bi 3+ After the source, the large pores and adsorption capacity of CAU-17 material are used to make Bi 3+Uniformly adsorbed in the pores and on the surface of CAU-17, and then a Br source was added to uniformly coat the generated BiOBr nanosheets on the CAU-17 nanorods by a solvothermal method. CAU-17 is a matrix that supports the growth of BiOBr. The close contact between CAU-17 and the BiOBr interface accelerates the separation of interfacial photogenerated electron-hole pairs and increases the specific surface area, thereby overcoming the recombination of carriers at the interface caused by the non-close contact of the heterogeneous interface, and significantly enhancing the photocatalytic activity of degrading organic dyes.

[0024] 2. Compared with BiOBr, the current density of transient photocurrent response of CAU-17 / BiOBr prepared by the present invention can reach up to 11.26μA / cm 2 The Nyquist circle diameter is small, it has a higher photocurrent response intensity, a smaller charge transfer resistance, a higher charge transfer efficiency, and a good photocatalytic degradation performance. It can efficiently degrade pollutants and has good adsorption capacity.

[0025] 3. The present invention adopts a solvothermal method to prepare CAU-17 / BiOBr catalyst material, which has simple operation, mild reaction conditions, low synthesis cost, and is suitable for mass production and large-scale application. The CAU-17 / BiOBr prepared by the present invention has good photocatalytic degradation ability for RhB and CIP, and the removal rates of RhB and CIP are 99.44% and 97.46% respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD patterns of CAU-17 and CAU-17 / BiOBr prepared in Example 1 and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0027] Figure 2 These are SEM images of CAU-17 and CAU-17 / BiOBr prepared in Example 1, and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0028] Figure 3 This is the SEM-EDS image of CAU-17 / BiOBr prepared in Example 1.

[0029] Figure 4 FT-IR graphs of CAU-17 and CAU-17 / BiOBr prepared in Example 1 and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0030] Figure 5UV-Vis DRS graphs of CAU-17 and CAU-17 / BiOBr prepared in Example 1 and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0031] Figure 6 These are transient photocurrent diagrams of CAU-17 and CAU-17 / BiOBr prepared in Example 1, and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0032] Figure 7 Electrochemical impedance spectroscopy of CAU-17 and CAU-17 / BiOBr prepared in Example 1 and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively.

[0033] Figure 8 1 is a graph showing the relationship between the residual RhB concentration and time in the photocatalytic degradation of RhB by CAU-17 / BiOBr in Example 1 and BiOBr and H3BTC / BiOBr in Comparative Examples 1-2.

[0034] Fig. 9 This is a diagram showing the adsorption and degradation of RhB in the photocatalytic degradation of RhB by CAU-17 / BiOBr in Application Example 1.

[0035] Fig.10 This is a bar graph showing the degradation rate of RhB after 6 cycles of photocatalytic degradation of RhB by CAU-17 / BiOBr in Application Example 1.

[0036] Fig.11 The graph is a relationship between the concentration of residual CIP and time in the photocatalytic degradation of CIP by CAU-17 / BiOBr in Example 2 and BiOBr and H3BTC / BiOBr in Comparative Examples 3-4.

[0037] Fig.12 It is a bar graph showing the degradation rates of RhB and CIP in the photocatalytic degradation of RhB and CIP by CAU-17 / BiOBr, BiOBr, and H3BTC / BiOBr in Application Examples 1-2 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.

[0039] Example 1

[0040] Preparation of CAU-17 / BiOBr composite photocatalyst:

[0041] (1) Preparation of CAU-17: 150 mg of Bi(NO3)3·5H2O and 750 mg of trimesic acid (H3BTC) were weighed and added to 60 mL of anhydrous methanol. The mixture was magnetically stirred at room temperature for 30 min until the reactants dissolved. The clear solution was then transferred to a hydrothermal reactor and heated at 120°C for 24 h. The resulting white powder was collected by filtration and washed twice with methanol to obtain CAU-17.

[0042] (2) Preparation of CAU-17 / BiOBr: 50 mg of CAU-17 was added to 10 mL of ethanol and ultrasonicated for 30 min to completely disperse it, obtaining a uniformly dispersed milky white suspension A; 485 mg of Bi(NO3)3·5H2O was dissolved in 10 mL of ethylene glycol and ultrasonicated for 10 min to obtain a clear and transparent solution B; solution B was slowly dripped into suspension A and stirred to obtain a uniformly dispersed milky white suspension C; 0.08 g of NaBr was dissolved in 10 mL of pure water and then dripped into suspension C and stirred for 30 min to obtain suspension D. Suspension D was transferred to a polytetrafluoroethylene high-temperature and high-pressure reactor and kept at 160°C for 12 h. The obtained light gray sample was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain a CAU-17 / BiOBr composite photocatalyst.

[0043] Example 2

[0044] Preparation of CAU-17 / BiOBr composite photocatalyst:

[0045] (1) Preparation of CAU-17: 150 mg Bi(NO3)3·5H2O and 700 mg trimesic acid were weighed and added to 60 mL anhydrous methanol. The mixture was stirred magnetically at room temperature for 30 min until the reactants were dissolved. The transparent solution was then transferred to a hydrothermal reactor and heated at 110°C for 24 h. The resulting white powder was collected by filtration and washed twice with methanol to obtain CAU-17.

[0046] (2) Preparation of CAU-17 / BiOBr: 50 mg of CAU-17 was added to 15 mL of ethanol and ultrasonicated for 30 min to completely disperse it, obtaining a uniformly dispersed milky white suspension A; 490 mg of Bi(NO3)3·5H2O was dissolved in 15 mL of ethylene glycol and ultrasonicated for 10 min to obtain a clear and transparent solution B; solution B was slowly dripped into suspension A and stirred to obtain a uniformly dispersed milky white suspension C; 0.07 g of NaBr was dissolved in 10 mL of pure water and then dripped into suspension C and stirred for 30 min to obtain suspension D. Suspension D was transferred to a polytetrafluoroethylene high-temperature and high-pressure reactor and kept at 150°C for 12 h. The obtained light gray sample was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain a CAU-17 / BiOBr composite photocatalyst.

[0047] Example 3

[0048] Preparation of CAU-17 / BiOBr composite photocatalyst:

[0049] (1) Preparation of CAU-17: 150 mg Bi(NO3)3·5H2O and 850 mg trimesic acid were weighed and added to 60 mL anhydrous methanol. The mixture was stirred magnetically at room temperature for 30 min until the reactants dissolved. The transparent solution was then transferred to a hydrothermal reactor and heated at 130°C for 22 h. The resulting white powder was collected by filtration and washed twice with methanol to obtain CAU-17.

[0050] (2) Preparation of CAU-17 / BiOBr: 50 mg of CAU-17 was added to 18 mL of ethanol and ultrasonicated for 30 min to completely disperse it, obtaining a uniformly dispersed milky white suspension A; 495 mg of Bi(NO3)3·5H2O was dissolved in 20 mL of ethylene glycol and ultrasonicated for 10 min to obtain a clear and transparent solution B; solution B was slowly dripped into solution A and stirred to obtain a uniformly dispersed milky white suspension C; 0.09 g of NaBr was dissolved in 10 mL of pure water and then dripped into suspension C and stirred for 30 min to obtain suspension D. Suspension D was transferred to a polytetrafluoroethylene high-temperature and high-pressure reactor and kept at 170°C for 10 h. The obtained light gray sample was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain a CAU-17 / BiOBr composite photocatalyst.

[0051] Comparative Example 1

[0052] Preparation of BiOBr: 485 mg Bi(NO3)3·5H2O was dissolved in 10 mL ethylene glycol, and after ultrasonic treatment for 10 min, a clear and transparent solution was obtained. 0.08 g NaBr was dissolved in 10 mL pure water and then added dropwise to the above solution. Stirring was continued for 30 min. The obtained solution was transferred to a high temperature and high pressure reactor and maintained at 160°C for 12 h. The obtained light gray sample was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain BiOBr.

[0053] Comparative Example 2

[0054] Preparation of H3BTC / BiOBr: 50 mg of trimesic acid was added to 10 mL of ethanol and ultrasonicated for 30 min to completely disperse it to obtain solution A; 485 mg of Bi(NO3)3·5H2O was dissolved in 10 mL of ethylene glycol and ultrasonicated for 10 min to obtain a clear and transparent solution B; solution B was slowly dripped into solution A and stirred to obtain solution C; 0.08 g of NaBr was dissolved in 10 mL of pure water and then dripped into solution C and stirred for 30 min to obtain solution D. Solution D was transferred to a high-temperature and high-pressure reactor and kept at 160°C for 12 h. The obtained light gray sample was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain H3BTC / BiOBr.

[0055] Material Characterization Analysis

[0056] (I) X-ray diffraction (XRD) analysis

[0057] X-ray diffractometer (XRD) was used to characterize CAU-17, CAU-17 / BiOBr prepared in Example 1 and BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2. Figure 1 As shown. Figure 1 It can be seen that the characteristic peaks of the sample prepared in Example 1 are consistent with the BiOBr standard card, and there is a strong diffraction peak of CAU-17 at the 10.2° peak, so the sample obtained in Example 1 is determined to be a CAU-17 / BiOBr material. The characteristic peaks of the sample prepared in Comparative Example 1 are consistent with the BiOBr standard card, so the sample obtained in Comparative Example 1 is determined to be a BiOBr material. The characteristic peaks of the sample prepared in Comparative Example 2 are consistent with the BiOBr standard card, so the sample obtained in Comparative Example 2 is determined to be a H3BTC / BiOBr material.

[0058] (ii) Scanning electron microscopy (SEM) analysis

[0059] The CAU-17 and CAU-17 / BiOBr prepared in Example 1 and the BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2 were characterized and analyzed using a scanning electron microscope (SEM). Figure 2 shown. Figure 2 (ad) SEM images of CAU-17 / BiOBr, CAU-17, BiOBr, and H3BTC / BiOBr, respectively. Figure 2 (a) It can be seen that the morphology of the CAU-17 / BiOBr material obtained in Example 1 is nanorod-like. Figure 3 EDS analysis shows the uniform distribution of Bi, Br, O, and C elements. It is worth noting that the Bi and Br elements are evenly dispersed on the nanorods, which further clearly verifies that a close contact interface is formed between CAU-17 and BiOBr, forming a structure in which BiOBr nanosheets are evenly coated on the CAU-17 nanorods. Figure 2 (b) It can be seen that the CAU-17 prepared in Example 1 exhibits a typical hexagonal prism-shaped nanorod structure. Figure 2 (c) It can be seen that the BiOBr material obtained in Comparative Example 1 exhibits a large two-dimensional nanosheet structure. Figure 2 (d) It can be seen that the H3BTC / BiOBr material obtained in Comparative Example 2 exhibits a two-dimensional nanoflower-like structure that is aggregated together.

[0060] (III) Fourier transform infrared spectroscopy (FT-IR) analysis

[0061] Fourier transform infrared spectrometer (FT-IR) was used to characterize the CAU-17 and CAU-17 / BiOBr prepared in Example 1 and the BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2, respectively. The characterization results are as follows: Figure 4 As shown. Figure 4 It can be seen that the CAU-17 prepared in Example 1 has a -1 and 1356cm -1 The two clear bands at 1537 cm -1 The band at 1681 cm-1 is attributed to the asymmetric vibration of the carboxylic acid functional group. -1 and 1356cm -1 The stretching vibration peaks of C=O and CO at 514 cm -1 The absorption peak of Bi-O was observed at 514 cm-1, indicating that the composite material sample was successfully prepared. -1The H3BTC / BiOBr prepared in Comparative Example 2 has a 1356cm-1 absorption peak belonging to H3BTC. -1 The CO stretching vibration peak at 1681 cm-1 of CAU-17 is not found. -1 The C=O stretching vibration peak at is 0.04, and there is no MOF in the structure.

[0062] (III) Ultraviolet visible diffuse reflectance spectroscopy (UV-Vis DRS) analysis

[0063] The CAU-17 and CAU-17 / BiOBr prepared in Example 1 and the BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2 were characterized and analyzed by UV-Vis DRS. The characterization results are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the absorption edge of CAU-17 is 319.88nm, and the light absorption range is narrow. The absorption edge of CAU-17 / BiOBr is 431.43nm, and the light absorption capacity is stronger than that of CAU-17. The absorption edge of BiOBr is 420.71nm. The absorption edge of H3BTC / BiOBr is 425.38nm.

[0064] (IV) Transient photocurrent (It) analysis

[0065] The CAU-17 and CAU-17 / BiOBr prepared in Example 1 and the BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2 were characterized and analyzed using a Bio / logic electrochemical workstation. Figure 6 As shown. Figure 6 It can be seen that the current density of the transient photocurrent response of CAU-17 / BiOBr can reach up to 11.26 μA / cm 2 , with a higher 2 )、BiOBr(0.67μA / cm 2 )、H3BTC / BiOBr(6.29μA / cm 2 ) higher photocurrent response intensity, which indicates that CAU-17 / BiOBr has a faster charge transfer efficiency.

[0066] (V) Electrochemical impedance spectroscopy (EIS) analysis

[0067] The CAU-17 and CAU-17 / BiOBr prepared in Example 1 and the BiOBr and H3BTC / BiOBr prepared in Comparative Examples 1-2 were characterized and analyzed using a Bio / logic electrochemical workstation. Figure 7 As shown. Figure 7It can be seen that CAU-17 / BiOBr has the smallest Nyquist semicircle diameter than CAU-17, BiOBr, and H3BTC / BiOBr, which indicates that the charge transfer resistance is the lowest in the CAU-17 / BiOBr material, which is conducive to the rapid transfer of charges.

[0068] Application Example 1

[0069] Take 20 mg of CAU-17 / BiOBr catalyst from Example 1 and disperse it into 50 mL of 10 -4 mol / L Rhodamine B (RhB) solution, magnetically stirred in the dark for 30 minutes to allow the mixed solution to reach the adsorption-desorption equilibrium between the photocatalyst and the pollutant. After turning on the light, irradiate the reactor under simulated sunlight, keep the distance between the reactor and the lamp at 6 cm, and take out 4 mL of the suspension every 3 minutes. After centrifugation to remove the catalyst, measure the absorbance of the supernatant by UV-visible spectrophotometer. Record the absorbance intensity of RhB at a wavelength of 553 nm. It can be calculated that the degradation rate of RhB by CAU-17 / BiOBr is 99.44%.

[0070] Application Comparative Example 1

[0071] The difference between Application Comparative Example 1 and Application Example 1 is that the catalyst used in Application Comparative Example 1 is BiOBr in Application Example 1, and the other reaction conditions are the same as those in Application Example 1. In the reaction, the degradation rate of BiOBr to RhB is 94.19%.

[0072] Application Comparative Example 2

[0073] The difference between Application Example 2 and Application Example 1 is that the catalyst used in Application Example 2 is H3BTC / BiOBr in Application Example 2, and the other reaction conditions are the same as those in Application Example 1. In the reaction, the degradation rate of RhB by H3BTC / BiOBr is 97.83%.

[0074] Application Example 2

[0075] Take 20 mg of the CAU-17 / BiOBr catalyst of Example 1 and disperse it in 50 mL of 20 mg / L ciprofloxacin (CIP) solution in a photoreactor, and stir it magnetically in the dark for 30 min to allow the mixed solution to reach the adsorption-desorption equilibrium between the photocatalyst and the pollutant. After turning on the light, irradiate the reactor under simulated sunlight, keep the distance between the reactor and the lamp at 6 cm, and take out 4 mL of the suspension every 10 min. After centrifugation to remove the catalyst, measure the absorbance of the supernatant by a UV-visible spectrophotometer. Record the absorbance intensity of CIP at a wavelength of 272 nm. It can be calculated that the degradation rate of CIP by CAU-17 / BiOBr is 97.46%.

[0076] Application Comparative Example 3

[0077] The difference between Application Example 3 and Application Example 2 is that the catalyst used in Application Example 3 is BiOBr in Comparative Example 1, and the other reaction conditions are the same as those in Application Example 2. In the reaction, the degradation rate of BiOBr to CIP is 90.39%.

[0078] Application Comparative Example 4

[0079] The difference between Application Comparative Example 4 and Application Example 2 is that the catalyst used in Application Comparative Example 4 is H3BTC / BiOBr in Comparative Example 2, and the other reaction conditions are the same as those in Application Example 2. In this reaction, the degradation rate of CIP by H3BTC / BiOBr is 93.07%.

[0080] Analysis of material catalytic performance

[0081] The effects of the catalysts in the application examples 1-2 and the application comparative examples 1-4 on the photocatalytic degradation of RhB and CIP were analyzed. The analysis results are as follows: Figure 8-12 shown. Figure 8 The relationship between the residual RhB concentration and time in the photocatalytic degradation experiment of RhB by CAU-17 / BiOBr, BiOBr, and H3BTC / BiOBr is shown. It is known that the direct photodegradation of RhB is almost negligible, and the degradation of RhB is caused by the oxidation of the photocatalyst added to the photocatalytic system under light. In the presence of the photocatalyst, as the xenon light irradiation time increases, CAU-17 / BiOBr has the best degradation effect, which is far superior to BiOBr and H3BTC / BiOBr, and the degradation of dye RhB can be completed in only 3 minutes.

[0082] Fig. 9 The adsorption and degradation of RhB in the photocatalytic degradation of RhB by CAU-17 / BiOBr. After 30 minutes of adsorption in the dark, the surface of CAU-17 / BiOBr turned purple-red and the solution was almost colorless, indicating the excellent adsorption capacity of the CAU-17 / BiOBr catalyst and the complete adsorption of the dye. After 3 minutes of illumination, in the system with CAU-17 / BiOBr as the photocatalyst, the absorbance of the characteristic peak of RhB was almost completely 0, the sample changed from purple-red to colorless, and the structure of RhB was destroyed and completely removed.

[0083] Fig.10 Figure 3 is the degradation rate of RhB photocatalytically degraded by CAU-17 / BiOBr after 6 cycles. After 6 cycles, CAU-17 / BiOBr still has a degradation rate of 97.61%, indicating that CAU-17 / BiOBr has good chemical stability.

[0084] Fig.11 The relationship between the residual CIP concentration and time in the photocatalytic degradation experiment of CIP by CAU-17 / BiOBr, BiOBr, and H3BTC / BiOBr is shown. In the blank control group, CIP was partially degraded over time without a photocatalyst, which may be the result of self-sensitization. The test results show that CAU-17 / BiOBr is much better than BiOBr and H3BTC / BiOBr in degrading CIP after illumination.

[0085] Fig.12 The degradation rates of CAU-17 / BiOBr, BiOBr, and H3BTC / BiOBr in the photocatalytic degradation of RhB and CIP were compared. The degradation rate of CAU-17 / BiOBr for CIP reached 97.46%, which was much higher than that of BiOBr (90.39%) and H3BTC / BiOBr (93.07%). The degradation rate of CAU-17 / BiOBr for RhB reached 99.44%, which was much higher than that of BiOBr (94.19%) and H3BTC / BiOBr (97.83%).

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A CAU-17 / BiOBr composite photocatalyst, characterized in that: Using CAU-17 as the matrix, adding Bi 3+ After the source, make Bi 3+ It is uniformly adsorbed on the surface of CAU-17, and then a Br source is added to make the generated BiOBr grow in situ on CAU-17 through a solvothermal reaction, and BiOBr is fixed on the framework of CAU-17 to obtain a CAU-17 / BiOBr composite photocatalyst.

2. The CAU-17 / BiOBr composite photocatalyst according to claim 1, characterized in that: The structure of the CAU-17 / BiOBr composite photocatalyst is a nanorod structure, and the BiOBr nanosheets are uniformly coated on the CAU-17 nanorods; the current density of the transient photocurrent response of the CAU-17 / BiOBr composite photocatalyst is 11.2-11.3 μA / cm 2 .

3. A method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of CAU-17: Bi(NO3)3·5H2O and trimesic acid were added to anhydrous methanol and stirred to dissolve at room temperature. The resulting mixed solution was transferred to a reactor for solvothermal reaction. After the reaction was completed, the product was collected by filtration and washed to obtain CAU-17. (2) Preparation of CAU-17 / BiOBr: CAU-17 was added to ethanol and dispersed completely by ultrasound to obtain suspension A. Bi(NO3)3·5H2O was dissolved in ethylene glycol and subjected to ultrasound to obtain solution B. Solution B was slowly dripped into suspension A and stirred to obtain suspension C. NaBr was dissolved in water and then dripped into suspension C and stirred continuously. The obtained suspension D was transferred to a reactor for solvothermal reaction. After the reaction was completed, the suspension was cooled to room temperature and centrifuged and washed to obtain a CAU-17 / BiOBr composite photocatalyst.

4. The method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 3, characterized in that: In step (1), the mass ratio of Bi(NO3)3·5H2O to trimesic acid is 1:4-6; the mass ratio of Bi(NO3)3·5H2O to anhydrous methanol is 5 mg:1.5-3 mL.

5. The method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 3, characterized in that: In step (1), the temperature of the solvent thermal reaction is 110 to 130° C. and the time is 22 to 24 hours.

6. The method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 3, characterized in that: In step (2), the mass ratio of CAU-17 to ethanol is 5 mg:1-2 mL; the mass ratio of Bi(NO3)3·5H2O to ethylene glycol is 48.5 mg:1-2 mL; and the mass ratio of CAU-17 to Bi(NO3)3·5H2O is 5:48-50.

7. The method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 3, characterized in that: In step (2), the mass ratio of NaBr to CAU-17 is 7 to 9:

5.

8. The method for preparing the CAU-17 / BiOBr composite photocatalyst according to claim 3, characterized in that: In step (2), the temperature of the solvent thermal reaction is 150-170° C. and the time is 10-12 hours.

9. Use of the CAU-17 / BiOBr composite photocatalyst as claimed in claim 1 or 2, characterized in that: The CAU-17 / BiOBr composite photocatalyst was used for photocatalytic degradation of rhodamine B and ciprofloxacin.

10. The use of the CAU-17 / BiOBr composite photocatalyst according to claim 9, characterized in that: The degradation rate of the CAU-17 / BiOBr composite photocatalyst for rhodamine B is 99.0-99.8%, and the degradation rate for ciprofloxacin is 97.0-97.8%.

Citation Information

Patent Citations

  • Bi / BiOBr (at) Bi-MOF heterojunction photocatalyst rich in oxygen vacancies as well as preparation method and application of Bi / BiOBr (at) Bi-MOF heterojunction photocatalyst

    CN117563582A

  • BiOCl / Bi-MOF heterojunction photocatalyst as well as preparation method and application thereof

    CN117732510A